Financial Policy in the Netherlands 1977-2002: The Effects of Fiscal Contracts - Eric Seils (Max Planck Institute for the Study of Societies, 2004)
The paper analyses the course of Dutch financial policy since the demise of Keynesian full employment. How did the public expenditure ratio, the tax burden, and the deficit develop in the last twenty-five years? Why did the government lose control over public spending in the period between 1977 and 1982, even though it proved possible to reduce spending continuously thereafter? Important explanatory variables in this context are economic growth and the ideological orientation of the government. In the 1990s, however, a literature on the common pool resource problem of public budgets developed which emphasizes the impact of the number of actors involved in financial policy-making as well as the institutional design of the budget process for public spending. Combining process tracing and intertemporal comparison, the study demonstrates how fiscal contracts were made and how they were stabilized through the working of the party system. It concludes that if other relevant variables are allowed for, fiscal contracts did have a moderating impact on public spending. – – In dem Papier wird die Finanzpolitik der Niederlande seit dem Ende der keynesianischen Vollbeschäftigungsphase analysiert. Wie haben sich die Staatsquote, die Abgabenquote und das Defizit in den vergangenen 25 Jahren entwickelt? Warum sind die Staatsausgaben in der Phase von 1977 bis 1982 praktisch unkontrolliert gewachsen, wenn es danach gelang, diese kontinuierlich zurück zu führen? Wichtige Erklärungsvariablen sind in diesem Zusammenhang natürlich das Wirtschaftswachstum und die ideologische Ausrichtung der Regierung. In den Neunzigerjahren hat sich eine Literatur zum Allmendeproblem des öffentlichen Haushaltes entwickelt, die zur Erklärung der Entwicklung der Staatsausgaben vor allem auf die Zahl der finanzpolitischen Akteure und die institutionelle Ausgestaltung des Haushaltsprozesses abstellt. Durch eine Kombination von Prozessanalyse und intertemporalen Vergleich wird gezeigt, wie finanzpolitische Vereinbarungen zu Stande kamen und wie sie durch die Funktionsweise des Parteiensystems stabilisiert wurden. Schließlich wird belegt, dass die in Koalitionsabkommen niedergelegten finanzpolitischen Absprachen unter Kontrolle anderer wichtiger Erklärungsvariablen einen mäßigenden Einfluss auf die Entwicklung der Staatsquote hatten.
Keywords: 300; Finanzpolitik; Policy-Ansatz; Staatsquote; Niederlande